Performance of green infrastructure for storm water treatment in cold climate (Canada). Issue 4 (26th April 2021) - Pineau, Béatrice; Brodeur-Doucet, Caroline; Corrivault-Gascon, Juliette; Arjoon, Diane; Lessard, Paul; Pelletier, Geneviève; Duchesne, Sophie
Abstract : Qualitative and quantitative treatment of storm water, through the implementation of best management practices, in particular green infrastructure (GI), can decrease run-off amounts and increase the quality of water in urban environments. In northern climates, however, climate change is leading to more rain in the winter months, when bioretention cells are full of snow, thereby potentially reducing the efficiency of installed GI. In this case study, at a site located near Montreal, Quebec, Canada, the environmental performance of a storm water treatment chain, composed of a bioretention cell and a retention pond, is estimated under winter conditions and compared with the performance of the bioretention cells alone. The results indicate that the bioretention cells were effective in removing total suspended solids, total phosphorus, lead, copper, zinc and hydrocarbons and decreasing total nitrogen, chemical oxygen demand and biological oxygen demand. Considering the good quality of the retention pond influent, little pollutant removal efficiency, if any, was added by this GI. The pond does, however, have a positive impact on the attenuation and shifting of peak flows, which should not be neglected. Overall, the results indicate that GI, particularly the bioretention cells, are active and effective in winter.